Menavigasi Dilema Etika Pendidikan di Era Kecerdasan Artifisial - Nailati, Izzah; Fitriatin, Nur; Nasywa, Azzah Iftitachun (Program Studi Manajemen Pendidikan Islam, 2023)
Digital transformation and artificial intelligence expand ethical dilemmas in education from classic issues to contemporary problems such as academic integrity, data privacy, algorithmic bias, and accountability of pedagogical decisions. This article aims to analyze the structure of these dilemmas, evaluate procedural code limitations, and develop an integrated decision making model with Islamic ethics. Through integrative literature review and conceptual normative analysis, the study finds that formal rule compliance is insufficient for resolving moral dilemmas. Decisions must be tested through multiple ethical lenses and public benefit. This article proposes the AMANAH Framework, comprising fact analysis, stakeholder mapping, multi lens assessment, maqasid substantive testing, shura, and accountable outcome documentation. This model contributes to updating professional codes, formulating artificial intelligence policies, and strengthening ethical literacy to ensure educational decisions remain centered on human dignity.